1994
DOI: 10.1006/aphy.1994.1012
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics with a Nonstandard Inertia-Acceleration Relation: An Alternative to Dark Matter in Galactic Systems

Abstract: We begin to investigate particle dynamics that is governed by a nonstandard kinetic action of a special form. We are guided by a phenomenological scheme-the modified dynamics (MOND)-that imputes the mass discrepancy, observed in galactic systems, not to the presence of dark matter, but to a departure from Newtonian dynamics below a certain scale of accelerations, a o . The particle's equation of motion in a potential φ is derived from an action, S, of the form S ∝ S k [ r(t), a o ] − φ dt. The limit a o → 0 co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
296
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(301 citation statements)
references
References 25 publications
4
296
1
Order By: Relevance
“…Milgrom (1994) has shown that within the modified inertia framework, Eq. (1) was exact only for circular orbits.…”
Section: Mond and Its Interpolating Functionmentioning
confidence: 99%
“…Milgrom (1994) has shown that within the modified inertia framework, Eq. (1) was exact only for circular orbits.…”
Section: Mond and Its Interpolating Functionmentioning
confidence: 99%
“…Milgrom (1994) showed that such theories always have to be time nonlocal to be Galilean invariant. As of this complication there is no full-fledged modified inertia theory developed yet (but see discussion in section 7.10 of Famaey & McGaugh 2012).…”
Section: Milgromian Dynamicsmentioning
confidence: 99%
“…See Milgrom [1994] for a comprehensive review. The basic idea was conceived by Milgrom [1983a], [1983b], [1983c], as a way of understanding the flat rotation curve phenomenology of spiral galaxies without recourse to the dark matter idea.…”
Section: Overview Of Mondmentioning
confidence: 99%